Beyond the individual: a qualitative case study into the systemic determinants of speaking-up behaviour in multidisciplinary team meetings - Jop Groeneweg; Jaco Tresfon; Daphne Roos; Irene Grossmann; Dimmy van Dongen; Frank Guldenmund (BMJ Open Quality)
Background Healthcare workers (HCWs) voicing their views (speaking up) is crucial for patient safety and care quality. Yet, this is underused, especially during multidisciplinary team meetings (MDTMs), where diverse professionals collaborate to optimise patient treatment plans. Despite the benefits of open communication, HCWs face barriers such as hierarchical dynamics, time constraints and psychological risks.Aim This study examines factors influencing HCWs’ speaking-up behaviours in MDTMs, focusing on motivators, barriers and dynamics across disciplines.Method We conducted 21 semistructured interviews with MDTM participants of a gastrointestinal surgery ward, including surgeons, residents, nurses, nursing students, dieticians, ostomy nurses and physical therapists. Data were analysed collaboratively using thematic analysis.Results Participants are highly motivated to advocate for patients and provide optimal care. However, barriers impact speaking up during MDTMs. Three major themes were identified: (1) time pressure, (2) perception of goals and roles and (3) familiarity among team members. Structural, relational and contextual factors affect HCWs’ ability to speak up, with nurses and paramedics experiencing more hesitancy than physicians. Lack of preparation time, ambiguous objectives, no formal agenda and unfamiliarity among team members hinder contributions, leading to unbalanced input.Conclusion Findings support a systems-based approach to addressing barriers. Interventions should focus on clear goals, reduced time pressures and enhanced team cohesion, rather than placing the responsibility solely on individuals. For instance, adjusting meeting schedules to accommodate diverse availability improves participation across disciplines. Strengthening familiarity among team members fosters trust and lowers the perceived risks of speaking up, ensuring more balanced contributions during MDTMs.